Historical Memory of the Lithuanian Anti-Soviet Partisan War in the Narratives of the Third Generation - Paskočiumaitė, Greta (Tautosakos darbai, 2021)
The article focuses on the historical memory maintained by the families of the members of the partisan armed anti-Soviet resistance in the 1944–1953. This memory is reconstructed on the grounds of the narratives by the third generation family members born in 1985–1989. The author discusses ways that memory of the partisan war is revealed by the generation born in the eve of restoration of the Lithuanian independence (which was proclaimed in 1990): how it was transferred in the families, and how experiences of the family members impacted and shaped the values and personal attitudes of the third generation towards the struggles for Lithuanian freedom. The analysis enables appreciating the influence that narratives established in the public discourse had in shaping the reflections of the family experiences, and pointing out, which images of the struggle for freedom are recognized by the third generation as suitable for the historical perception. It is noted that stories by the third generation make use both of the family narratives and the available public information.The interviewed informants usually do not remember the moment when they first learned of their family members’ participation in the armed resistance and their subsequently suffered repressions. For many, it was an inherent part of their daily life that shaped their attitudes towards the history of deportations, imprisonments, and Holocaust. Usually, the biographical facts of the family members were highlighted in various situations of the daily life, and their authentic and real stories reminded those of the fictional heroes. Narratives maintained in the family were accepted as very important to the family members; however, their certification or supplementation required other sources. The third generation can be characterized by their attempts to seek the historical truth and strive for justice. They attempt at getting to know the “un-heroic” picture of the postwar resistance, uncovering the obscure historical details, and ensuring continuation of the memory, which they try to pass on not only to the younger generations of the family, but also to the outsiders. This generation performs the role of mediator between the first and the second ones in their attempts both at understanding the past and at reconciliation with it.This generation exhibits an ambivalent attitude towards the history of the partisan war. On the one hand, they try assuming an unbiased position, but evidently, the family past strongly influences their values and behavior. The third generation displays considerable empathy towards participants of the historical events and their diverse fates. The narrators tend to emphasize their patriotism and appreciation of this land and its freedom, of gaining inner strength from the historical struggles for freedom. In some cases, the narrators describe themselves as belonging to the partisan community. All the narratives are characterized by enhanced importance of freedom as a universal value, which content, however, depends on the individual experience and understanding. Active involvement of this generation into the commemoration of the partisan resistance is encouraged not only by their family history, but also by the public opinion.The generation that grew up in the independent Lithuania had an unrestricted access to the history of the armed resistance. Nowadays its representatives willingly and openly share not only their own experiences, but also those of their family members. In spite of their declared unbiased attitude, they display pride in their family history and readiness to foster it.
Keywords: historical memory; narrative; partisan war; partisans; third generation